Long-term COVID symptoms, work ability and fitness to work in healthcare workers hospitalized for Sars-CoV-2 infection - Mendola, Marco; Leoni, Marco; Cozzi, Ylenia; Manzari, Andrea; Tonelli, Fabio; Metruccio, Francesca; Tosti, Luca; Battini, Vera; Cucchi, Isabella; Costa, Maria Cristina; Carrer, Paolo (La Medicina del Lavoro, 2022)
Background: COVID-19 can affect the persistence of symptoms and work ability (WA), hence the fitness to work of healthcare workers (HCW). We describe the effects of COVID-19 in hospitalized HCWs of a large Hospital in Lombardy and their implications on WA and fitness to work. Methods: Fifty-six HCWs of Fatebenefratelli-Sacco Hospital have been hospitalized for COVID-19 since March 2020. Clinical and fitness-to-work data were acquired from Occupational Health Surveillance Program. A structured questionnaire was administered to 53/56 HCWs 18 months after infection to investigate Long-COVID symptoms and WA. Results: Symptoms most reported at recovery (rhino-pharyngeal swab-NPS-negative) were exertional dyspnea (86.8%), asthenia (86.8%), arthro-myalgia (71.7%), sleep disorders (64.2%), resting dyspnea (62.3%), cough (56.6%). 69.6% underwent evaluation at out-patient clinics experienced in Long-COVID. Ten months after recovery, symptoms related to physical well-being decreased while memory and anxiety/depression were more persistent. At recovery, the WA score decreased from 10 to 8, and then an improvement from 8 to 9 was noted during the survey. At the return-to-work examination, fit-to-work judgements with restrictions increased from 31.4% to 58.7%; then, a slight decrease in the rate of judgements with restrictions was observed at the survey’s time. Conclusion: Post-COVID-19 symptoms can persist for a long time and could impact WA and fitness-to-work of HCW. Adequate health surveillance protocols should guarantee the health protection of HCW with persistent disorders after COVID-19.